Perancangan Sistem Informasi Pelaporan Gangguan Dan Restitusi Pelanggan Internet Corporate Berbasis Web (Studi Kasus Di PT. Indosat Mega Media West Regional) - Tukino Tukino (Teknik Informatika, 2018)
The development of the world of technology and information today requires us to always have information and manage the information itself, no wonder if now many organizations pay attention to the processing of information systems they have. Coupled with the support of technology such as computers that become supporters in data processing to produce information needed an organization quickly and accurately, as well as the increasing number of human resources capable of performing data processing. In PT Indosat Mega Media Regional West can not be said to manage the information well because the processing of data disturbance reports and calculation of customer restitution is still considered very slow in the presentation of information. In addition, the resulting information is less than optimal, ineffective and inefficient. This happens because the data processing data disturbance at PT Indosat Mega Media Regional West still use semi-manual system, where there is no information system that can perform data access, delivery of information and data storage in a database, in this case data disturbance and customer restitution . It is on this basis that the authors do research and design a database oriented application program capable of performing data interruption of the internet on the work function of NOC (Network Operation Center) in PT Indosat Mega Media West Regional.